ANALISIS EMPIRIS MULTIMEDIA INTERAKTIF KONSEP DAN FENOMENA KUANTUM SEBAGAI MEDIA PEMBELAJARAN FISIKA - Triani, Trisna Be; Nasir, Muhammad; Zulirfan, Zulirfan (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to describe the results of interactive multimedia empirical analysis used for physics learning concept material and quantum phenomena for grade XII students of SM /MA includes validity and reliability. This type of research is a survey study, with the implementation procedure referring to research procedures developed according to the important steps in survey research. The subjects in this study are students of class XII MIA 1 MAN 2 Model Pekanbaru that consist of 14 male and 12 female students. The data in this research is a score of multimedia assessment given to the respondents through questionnaires that consist of display aspect, pedagogic aspect, content aspect and technical aspect. Furthermore the data is analyzed by validity test through Product Moment correlation technique and the average formula, while reliability test through cronbach's alpha technique. According to the data analysis, the validity of the scores of all respondents to interactive multimedia is greater than critical r with the result that every aspect is declared valid. Reliability’s score for all respondents to interactive multimedia has a value of cronbach's alpha is greater than 0,7 videlicet = 0.951. It can be concluded that interactive multimedia concepts and quantum phenomena are empirically declared valid and reliable. Eventually, it is feasible to be used for physics learning media in SMA/MA.Keywords: Empiris Analysis, Interactive Multimedia, The Concept and Quantum Phenomena